Media Pembelajaran Video dan Poster Untuk Meningkatkan Kreativitas Siswa Serta Guru SMK Negeri 1 Bungo - toyib, rozali; Kharisma , Agung; Darnita, Yulia; Muntahanah, Muntahanah; Wijaya, Ardi; Witriyono, Harry (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
Learning media requires creativity from both students and teachers. It is very important to be able to organize visually appealing class materials such as presentations, posters, group activities, virtual class materials such as Zoom or Google Meet backgrounds, class decorations, infographics, video templates and any other materials that require special training so that teachers and students can discuss using Canva in making learning media and posters, being creative and artistically independent. This community service aims to provide innovation to students and teachers to produce high-quality graphic designs with minimal effort, and the Merdeka curriculum includes digitization elements that encourage teachers and students to be more creative in teaching through various platforms available in cyberspace. and learning needs. The method or approach used in the PKM program activities includes development training on learning media and making posters using Canva for students and teachers. Conclusion: the level of teacher participation in activities is high, teachers can be trained for training, they can use learning resources during training in teaching and educational activities in schools, ongoing training with future topics is currently needed.